Pengaruh Kinerja Keuangan dan Ukuran Perusahaan Terhadap Income Smoothing - Jamaluddin, Jamaluddin; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the influence of financial performance and firm size to the income smoothing on the real estate and property companies which are listed in Indonesia Stock Exchange during 2012-2013 periods. The samples have been selected by using purposive sampling technique and eckel index calculation, so 30 real estate and property companies which have met the criteria have been selected. The analysis technique has been done by using multiple regressions and SPSS program 16 version. Based on the result of multiple regressions analysis with the significance level is 5%, then the result shows i.e.: 1) Debt to Equity Ratio does not have any influence to the income smoothing, 2). Net Profit Margin has influence to the income smoothing, 3). Return on Asset has influence to the income smoothing, 4). Firm size has influence to the income smoothing. Therefore, Debt to Equity Ratio does not have any influence to the income smoothing whereas net profit margin, return on asset, and firm size have influence to the income smoothing.Keywords: Financial Performance, Firm Size, and Income Smoothing